2020
DOI: 10.1101/2020.06.01.127126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A miR-124-mediated post-transcriptional mechanism controlling the cell fate switch of astrocytes to induced-neurons

Abstract: 26miR-124 plays a major regulatory role in neurogenesis and neuronal differentiation during 27 brain development through control of its multiple non-neuronal targets and has therefore 28 been employed in direct reprogramming protocols supplementary to neurogenic TFs, and 29 other miRNAs to enhance neurogenic conversion. However, its capacity to instruct 30 neurogenic conversion of astrocytes and its independent mechanism of direct 31 reprogramming action have been poorly investigated. Aim of the study was to i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 98 publications
(253 reference statements)
0
6
0
Order By: Relevance
“…We further leveraged pyPAGE for the inference of regulatory programs hidden in the bulk data and uncovered characteristic upregulation of developmental TF regulons in most of the cell types. Similarly, we have identified that miR-124-3p, one of the key miRNAs that is depleted in AD brains, most strongly affects astrocytes, which might block their transdifferentiation into neurons 91 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We further leveraged pyPAGE for the inference of regulatory programs hidden in the bulk data and uncovered characteristic upregulation of developmental TF regulons in most of the cell types. Similarly, we have identified that miR-124-3p, one of the key miRNAs that is depleted in AD brains, most strongly affects astrocytes, which might block their transdifferentiation into neurons 91 .…”
Section: Discussionmentioning
confidence: 79%
“…Astrocytes showed a significant increase in the stability of miR-124-3p and miR-506-3p regulons, which are similarly critical for astrocytes transdifferentiation into neurons 91 and neuronal proliferation 92 . The key observation that most prominent patterns of miRNA and RBP regulons perturbations occur in non-neuronal cells highlights the importance of glia in AD pathology.…”
Section: Cell-type Specific Analysis Of Post-transcriptional Regulato...mentioning
confidence: 99%
“…60,61 Second, studies have shown one mechanism that miR-124-3p inhibits astrocyte activation or switches the astrocytes into induced neurons, wherein autophagy, ER stress, PI3K/AKT/NF-κB, and ARE-mediated mRNA decay signals are considered to be involved. 22,24,62 To establish associations among miR-124-3p, astrocyte activation, and potential target genes, we performed a literature review of the study topic. In astrocytes, Elovl mediates the production of long-chain saturated fatty acids, and Smad2 is associated with autophagy.…”
Section: ■ Discussionmentioning
confidence: 99%
“…66, 68, 79 Moreover, overexpression of miR-124 has been shown to reprogram somatic cells into neurons. 80, 81 It should be noted that these aforementioned functions are regulated by the well-studied miR-124-3p. In contrast, here we showed that mature miR-124-5p, but not miR-124-3p, acted to regulate optic nerve regeneration, revealing a novel function of miR-124.…”
Section: Discussionmentioning
confidence: 99%